Moscatilin Reverses EMT Progression and its Resulting Enhanced Invasion and Migration by Affecting the TGF-β Signaling Pathway in Bladder Cancer - Li, Zhihao; Yang, Jin; Chen, Lin; Chen, Pei; Liu, Chenhuan; Long, Xiaoming; Chen, Bo; Long, Jun (Anti-Cancer Agents in Medicinal Chemistry, 2024)
Background: Bladder cancer metastasis is an essential process in the progression of muscle-invasive bladder cancer. EMT plays a crucial role in facilitating the spread of cancer cells. Identifying compounds that can inhibit these abilities of cancer cells is a significant international endeavor. Objective: To explore the migration and invasion effect of Moscatilin on the bladder and clarify the mechanism of action Methods: The anti-bladder cancer effect of Moscatilin was observed by a cell proliferation experiment. The migration and invasion of bladder cancer cells inhibited by Moscatilin were detected by Transwell and Wound healing. The effects of Moscatilin on EMT-related proteins E-cadherin, N-cadherin, Snail1, Vimentin, and TGF-β signaling pathways were detected by Western blot, and nucleic acid levels were verified by qPCR. Results: Our study revealed that Moscatilin reduced the viability of bladder cancer cells in vitro and impeded their migration and invasion in experimental settings. Furthermore, we observed that Moscatilin decreased the activation levels of active proteins, specifically Smad3, Samd2, and MMP2. Additionally, we found that moscatilin significantly reduced the expression level of TGF-β and was also capable of reversing the overexpression effect of TGF-β. Treatment with Moscatilin also led to significant inhibition of interstitial cell markers Ncadherin and Snail1, which are associated with EMT. Conclusion: These findings indicate that Moscatilin impedes the migration and invasion of bladder cancer cells by influencing cell survival, modulating TGF-β/Smad signaling, and inhibiting EMT.
Keywords: Bladder cancer